Pengaruh Kondisi Keuangan, Disclosure, Opini Audit pada Tahun Sebelumnya Terhadap Opini Audit Going Concern (Studi Kasus pada Perusahaan Wholesale and Retail Trade di BEI Tahun 2019-2020) - Ririn Wahyuni; Dwi Ari Pertiwi (JFAS : Journal of Finance and Accounting Studies, 2022)
The purpose of this research is to find out the influence of financial conditions, disclosures and audit opinions during the previous year on the Going Concern Audit Opinion in Wholesale and Retail Trade companies listed on the IDX in 2019-2020. The sample technique in this research is using purposive sampling technique and obtained a sample of 66 Wholesale and Retail Trade companies listed on the IDX in 2019-2020. Logistic regression method was used to analyze the data in the study. The results of the study indicate that financial conditions have no effect on going concern audit opinion, this is represented by a significance value of 0.700 which is greater than 0.05. Meanwhile, the disclosure has an impact on the going concern audit opinion with the resulting value being 0.000 less than 0.05, and last year's audit opinion does not affect the going concern audit opinion, because the significance value is 0.290 greater than 0.05.  Keywords: Financial Conditio; Disclosure; Audit Opinion in Previous Year; Audit Opinion Going Concern